Role of Banks in Promoting Financial Literacy among Agripreneurs in Assam, India. - Newar, Purnima; Bhuyan, Anjan (Journal of Agricultural Extension, 2022)
This paper examined financial literacy services provided by banks to agripreneurs and the associated problems. Participants were 500 agripreneurs and 250 bank managers, selected using a multi-stage sampling design in Assam, a north-eastern state of India. The result showed that out of 19 identified variables of financial literacy services, the degree of awareness of agripreneurs by banks is marked very low in 17 variables. In 7-point rating scale, average score of lack of manpower, difficulty in reaching the target group and poor coverage of topics was more than 3.5 which categorised them as major hindrances in conducting Financial Literacy Programme (FLP), particularly for agripreneurs. However, consideration of both organisational and operational approaches is suggested for better implementation of FLP for agripreneurs.